Effects of resistance training, detraining and retraining on myofibrillar and sarcoplasmic protein profiles: A LC-MS -based proteomics study - Rissanen, Elias (2025)
Introduction. Proteomics appears as a modern discipline to produce deep-level adaptations of human skeletal muscle to resistance training. However, alterations of muscle fiber protein profiles during detraining and retraining remain poorly investigated. Additionally, a clear consensus of myofibrillar and sarcoplasmic protein classification appears to be lacking. Therefore, the present thesis demonstrates an alternative approach to classification of protein profiles and seeks the impact of training and detraining periods on myofibrillar and sarcoplasmic protein profiles while muscle size is altered.